2002
DOI: 10.1093/nar/gkf441
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of repeatability in spotted cDNA microarrays

Abstract: We report a strategy for analysis of data quality in cDNA microarrays based on the repeatability of repeatedly spotted clones. We describe how repeatability can be used to control data quality by developing adaptive filtering criteria for microarray data containing clones spotted in multiple spots. We have applied the method on five publicly available cDNA microarray data sets and one previously unpublished data set from our own laboratory. The results demonstrate the feasibility of the approach as a foundatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…For example, the reported Pearson correlation coefficient between technical replicates can range between the disappointing level of 0.5 and the more reassuring level of 0.95. [148][149][150] Cross-platform reproducibility studies undertaken so far 148,149,151 have identified two main problems. First, microarrays are not able to accurately measure genes expressed at low levels.…”
Section: Reproducibilitymentioning
confidence: 99%
“…For example, the reported Pearson correlation coefficient between technical replicates can range between the disappointing level of 0.5 and the more reassuring level of 0.95. [148][149][150] Cross-platform reproducibility studies undertaken so far 148,149,151 have identified two main problems. First, microarrays are not able to accurately measure genes expressed at low levels.…”
Section: Reproducibilitymentioning
confidence: 99%
“…Several methods for analysis of differential gene expression exist, including microarrays, LuxArray, and differential fluorescence induction. Complications of microarray analysis include its reproducibility and standardization (9,10,21,24,27,44). Differential fluorescence induction uses flow cytometry to select bacteria containing transcriptionally active regulatory regions cloned upstream of a promoterless green fluorescence protein (GFP) reporter gene (29,43,(48)(49)(50); however, there are technical challenges associated with sorting bacteria.…”
mentioning
confidence: 99%
“…A 60% similarity in the reproducibility of the technical replicates was proposed acceptable in other studies, and it has been reported that the correlation coefficient can range between 0.5 and 0.95 (this corresponds to 50 -95%) (Bammler et al, 2005) (Jarvinen et al, 2004) (Jenssen et al, 2002) (Carter et al, 2005).…”
Section: Section 431 Optimization Of the Microarray Techniquementioning
confidence: 83%